Efficient modeling of masonry failure using a multiscale domain activation approach. (15th July 2021) - Driesen, Cedric; Degée, Hervé; Vandoren, Bram
Highlights: Multiscale modeling can both accurately and efficiently simulate masonry facades. The proposed method can be applied to more complex masonry systems. The efficiency increase is often higher in larger scale structures. Abstract: A finite element based framework that formulates an adaptive multiresolution multiscale technique is presented, with the goal of both accurately and efficiently simulating large masonry structures. In order to find a compromise between accuracy and computational efficiency a scale embedding multiscale model where both macro- and microscale elements come into play is proposed, combining the advantages both have to offer. This theory is tested and compared with an equivalent microscale model to demonstrate that its accuracy rivals a microscale approach, while at the same time having a higher computational efficiency. The developed multiscale model is compared to its underlying microscale model in a couple of selected example structures, ranging from small to large scale unreinforced masonry walls with openings. An application in the form of soil subsidence is explored, showing a potential for extended applications of this type of modeling.